Immune responses and growth performance of catfish (Clarias gariepinus Burchell 1822) cultivated in bioflok system with different carbon sources and infected with Aeromonas hydrophila - Windu Sukenda; Widanarni Widanarni; Mia Setiawati (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2016)
One of the diseases that often attack the catfish is motile aeromonas septicemia (MAS) caused by Aeromonas hydrophila. This study aimed to evaluate the immune responses and growth performance of catfish that cultivated on biofloc systems with different carbon sources and infected by A. hydrophila. This study was conducted over 30 days, consists of five treatments with three replications viz., providing molasses carbon source (A), tapioca flour (B), wheat flour (C), positive control (D) and a negative control (E). The results showed that the immune response such as total erythrocytes, hematocrit, hemoglobin concentration, total leukocyte, phagocytic activity, and respiratory burts activity at molasses (A), tapioca flour (B),and wheat flour (C) treatment showed better results than the control. Carbon sources from molasses, tapioca and wheat were able to increase total bacteria and decrease the growth of A. hydrophila in the waters as well as in catfish organs. Catfish growth performance in biofloc system with tapioca flour carbon source provide daily growth rate which was higher and significantly different (p <0.05) than control. While the biofloc system with molasses, tapioca and wheat carbon source could decrease feed conversion ratio and increase the retention of the protein. Retention of lipid in the biofloc system with molasses carbon source showed the highest results. The addition of molasses, tapioca and wheat as carbon sources into bioflock system could reduce the abundance of A. hydrophila, while immune response and growth performance of catfish increase well. Abstrak Salah satu penyakit yang sering menyerang ikan lele adalah Motil Aeromonad Septicemia yang disebabkan oleh bakteri Aeromonas hydrophila. Penelitian ini bertujuan untuk mengevaluasi respon imun dan kinerja pertumbuhan ikan lele yang dibudidayakan pada sistem bioflok dengan sumber karbon yang berbeda serta diinfeksi oleh A. hydrophila. Peneli- tian dilakukan selama 30 hari, menggunakan rancangan acak lengkap yang terdiri atas lima perlakuan dengan tiga ulangan yaitu penambahan sumber karbon molase (A), tepung tapioka (B), tepung terigu (C), kontrol positif (D), dan kontrol negatif (E). Hasil penelitian menunjukkan bahwa respon imun seperti total eritrosit, hematokrit, kadar hemoglo- bin, jumlah leukosit, aktivitas fagositosis, dan ledakan pernapasan pada perlakuan molase (A), tepung tapioka (B), dan tepung terigu (C) menunjukkan hasil yang lebih baik daripada kontrol. Sumber karbon molase, tapioka, dan terigu mampu meningkatkan total bakteri dan menekan pertumbuhan A. hydrophila di air dan organ ikan lele. Kinerja pertum- buhan ikan lele di sistem bioflok dengan sumber karbon tepung tapioka memberikan laju pertumbuhan harian yang le- bih tinggi dan berbeda nyata (P <0,05) dibandingkan kontrol. Sistem bioflok dengan sumber karbon molase, tapioka, dan terigu dapat menurunkan nisbah konversi pakan dan meningkatkan retensi protein. Retensi lemak dalam sistem bio- flok dengan sumber karbon molase menunjukkan hasil tertinggi. Penambahan sumber karbon molase, tapioka, dan teri- gu dalam sistem bioflok dapat menurunkan kelimpahan A. hydrophila dan meningkatkan respon imun dan kinerja per- tumbuhan ikan lele.